Sprinting ability as an important indicator of performance in elite long-distance runners - Yamanaka, R.; Ohnuma, H.; Ando, R.; Tanji, F.; Ohya, T.; Hagiwara, M.; Suzuki, Y. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Increases in maximal oxygen uptake (V.O2max) and running economy improve performance in long-distance runners. Nevertheless, long-distance runners require sprinting ability to win, especially in the final phase of competitions. The authors determined the relationships between performance and sprinting ability, as well as other abilities in elite long-distance runners. Methods: The subjects were 12 elite long-distance runners. Mean official seasonal best times in 5000-m (5000 m-SB) and 10,000-m (10,000 m-SB) races within 1 year before or after the examination were 13:58.5 (0:18.7) and 28:37.9 (0:25.2) (mean [SD]), respectively. The authors measured 100-m and 400-m sprint times as the index of sprinting ability. They also measured V.O2max and running economy (V.O2 at 300 m/min of running velocity). They used a single correlation analysis to assess relationships between 5000 m-SB or 10,000 m-SB and other elements. Results: There were significant correlations between 5000 m-SB was significantly correlated with 100-m sprint time (13.3 [0.7] s; r=.68, P=.014), 400-m sprint time (56.6 [2.7] s; r=.69, P=.013), and running economy (55.5 [3.9] mL/kg·min; r=.59, P=.045). There were significant correlations between 10,000 m-SB and 100-m sprint time (r=.72, P=.009) and 400-m sprint time (r=.85, P<.001). However, there was no significant correlation between 5000 m-SB or 10,000 m-SB and V.O2max (72.0 [3.8] mL/kg-min). Conclusions: The authors' data suggest that sprinting ability is an important indicator of performance in elite long-distance runners.